Predatory Journals: A Threat to Scholarly Publishing - Shrestha, Jiban; Subedi, Subash; Shokati, Behzad; Chaudhary, Amit (Journal of Education and Research, 2018)
Nowadays the world of scholarly publishing is in serious trouble because of the increasing number of predatory publishing. Besides, citation of articles from predatory journals is also unethical that undermines the quality of research papers. Because of ignorance of predatory publishing and/or compulsion of getting published in a limited time, scholars from Universities and young researchers become victim to predatory or hijacked journals. The purpose of this paper is to create awareness among authors, especially novice ones, about predatory publication. Research institutions should encourage their researchers to publish their articles in valuable journals indexed in Web of Science’s Journal Citation Reports (JCR), Clarivate Analytics, formerly part of Thomson-Reuters) or other famous scientific databases such as Scopus, PubMed and MEDLINE. In this way, attention to the Thomson Reuters’ Journal Impact Factor (JIF) and Journal Ranking (JRK) and Scopus grade (Q1, Q2 and Q3) may be useful and necessary.